Compression map, functional groups and fossilization: A chemometric approach (Pennsylvanian neuropteroid foliage, Canada) - D`angelo, José Alejandro (2012)
Nearly all of the spectrochemical studies involving Carboniferous foliage of seed-ferns are based on a limited number of pinnules, mainly compressions. In contrast, in this paper we illustrate working with a larger pinnate segment, i.e., a 22-cm long neuropteroid specimen, compression-preserved with cuticle, the compression map. The objective is to study preservation variability on a larger scale, where observation of transparency/opacity of constituent pinnules is used as a first approximation for assessing the degree of pinnule coalification/fossilization. Spectrochemical methods by Fourier transform infrared spectrometry furnish semi-quantitative data for principal component analysis. The compression map shows a high degree of preservation variability, which ranges from comparatively more coalified pinnules to less coalified pinnules that resemble fossilized-cuticles, noting that the pinnule midveins are preserved more like fossilized-cuticles. A general overall trend of coalified pinnules towards fossilized-cuticles, i.e., variable chemistry, is inferred from the semi-quantitative FTIR data as higher contents of aromatic compounds occur in the visually more opaque upper location of the compression map. The latter also shows a higher condensation of the aromatic nuclei along with some variation in both ring size and degree of aromatic substitution. From principal component analysis we infer correspondence between transparency/opacity observation and chemical information which correlate with varying degree to fossilization/coalification among pinnules.